2002
DOI: 10.2527/2002.8071939x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Quillaja saponaria extract on growth performance and immune function of weanling pigs challenged with Salmonella typhimurium1

Abstract: Ninety-six pigs (initially 8.9 kg and 24 d of age) were used in a 28-d experiment to determine the effects of Quillaja saponaria extract (QS) on weanling pig growth performance and immune function in response to enteric disease challenge with Salmonella typhimurium (ST). Experimental treatments were arranged in a 2 x 4 factorial with main effects of disease challenge (control vs ST-challenge) and dietary addition of QS (0, 125, 250, or 500 mg/kg). Pigs were fed QS diets for 14 d and then challenged orally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
3
23
0
3
Order By: Relevance
“…Our results revealed that oral exposure to S. Typhimurium and S. Enteritidis led to an~10% reduction in growth, which was likely explained by a reduction in feed intake (4% by S. Typhimurium group and 11% by S. Enteritidis group) as the level of feed intake is a basic and important factor that determines the rate of growth and body composition achieved by animals during their lifecycles (Richards, 2003). This observation is in agreement with those of previous studies by Balaji et al (2000), Turner et al (2002) and Burkey et al (2004) who reported lower feed intake and growth rate in pigs orally challenged with S. Typhimurium. However, to the best of our knowledge, no other studies of the effect of oral infection with S. Enteritidis on the growth performance of pigs have been conducted to date.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that oral exposure to S. Typhimurium and S. Enteritidis led to an~10% reduction in growth, which was likely explained by a reduction in feed intake (4% by S. Typhimurium group and 11% by S. Enteritidis group) as the level of feed intake is a basic and important factor that determines the rate of growth and body composition achieved by animals during their lifecycles (Richards, 2003). This observation is in agreement with those of previous studies by Balaji et al (2000), Turner et al (2002) and Burkey et al (2004) who reported lower feed intake and growth rate in pigs orally challenged with S. Typhimurium. However, to the best of our knowledge, no other studies of the effect of oral infection with S. Enteritidis on the growth performance of pigs have been conducted to date.…”
Section: Discussionsupporting
confidence: 92%
“…Tracking APR provides useful measures of clinical or sub-clinical manifestations in pigs challenged with enteric pathogens (Turner et al 2002;Burkley et al 2004;Houdijk et al 2007). Therefore, the present study evaluated APR in pigs fed HP and EYA upon oral challenge with ETEC.…”
mentioning
confidence: 99%
“…Dietary treatment with crude soap bark of Q. saponaria, ranging from 125 to 500 mg/kg, did not counteract the negative effects on feed intake and growth induced transiently by a challenge with Salmonella enterica serovar Typhimurium (Turner et al, 2002b). Q. saponaria also failed to modulate the rise in serum haptoglobin, a-1-acid glycoprotein and IgM concentrations induced by this challenge 7 and 14 days postinfection (Turner et al, 2002b). The phagocytic function of peripheral white blood cells tended to be depressed in challenged pigs fed with high doses of Q. saponaria, but not with low doses (Turner et al, 2002b).…”
Section: In-feed Modulators Of Piglet Immunitymentioning
confidence: 85%
“…Q. saponaria also failed to modulate the rise in serum haptoglobin, a-1-acid glycoprotein and IgM concentrations induced by this challenge 7 and 14 days postinfection (Turner et al, 2002b). The phagocytic function of peripheral white blood cells tended to be depressed in challenged pigs fed with high doses of Q. saponaria, but not with low doses (Turner et al, 2002b). It has been suggested that these 'weak immune modulations' may be due to the low purity of the extract used (Ilsley et al, 2005), which could reach a maximal level of 10% of saponins.…”
Section: In-feed Modulators Of Piglet Immunitymentioning
confidence: 86%
See 1 more Smart Citation